Disability Hate Crime: The Overlooked Consequence of the Deinstitutionalization of Care - Šumskienė, Eglė (Socialinė teorija, empirija, politika ir praktika, 2017)
Both disability hate crime and institutional violence are major violations of the rights of persons with intellectual disabilities. This article aims to discuss both forms of violence in the context of deinstitutionalization of care in the countries of Eastern and Central Europe1 and the prevailing high rates of discriminatory attitudes in this region. This paper follows a contextualized approach toward discrimination and invokes predominant attitudes in the societies of the region as one particular aspect of the general context. This approach helps to estimate the potential threats for residents of social care institutions to experience hate crime in the community. Residential care institutions are criticized for high rates of institutional violence; nevertheless, the transfer of residents to community care may expose them to hate crimes in the community. This aspect of deinstitutionalization neither appears on the public and political agenda, nor is it being analyzed by academia in the region. This paper draws attention to important consequences of deinstitutionalization, which possibly have been overlooked by the promoters of deinstitutionalization as well as by the disability policy makers in the region. This composes the originality and practical value of the paper.